Green Investment Appraisal: A Comprehensive Framework for Evaluating Environmental and Financial Returns - Purwanti, Ari (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This article presents a comprehensive framework for evaluating green investments, considering environmental impacts and financial outcomes. This framework is designed to assist decision-makers in identifying projects that provide high financial returns while considering positive environmental impacts. The proposed green investment evaluation methods include net present value (NPV), internal rate of return (IRR), and cost-benefit analysis, which considers the economic value of environmental impacts. The proposed green investment evaluation method includes Net Present Value (NPV) and Internal Rate of Return (IRR), tools commonly used in financial assessment. This framework also considers a cost-benefit analysis that includes the economic value of environmental impacts. These results allow stakeholders to consider energy savings, carbon emission reduction, and the social impact of green investment projects.